Factors associated with low adherence to medicine treatment for chronic diseases in Brazil - Noemia Urruth Leão Tavares; Andréa Dâmaso Bertoldi; Sotero Serrate Mengue; Paulo Sergio Dourado Arrais; Vera Lucia Luiza; Maria Auxiliadora Oliveira; Luiz Roberto Ramos; Mareni Rocha Farias; Tatiane da Silva Dal Pizzol
ABSTRACT OBJECTIVE To analyze factors associated with low adherence to drug treatment for chronic diseases in Brazil. METHODS Analysis of data from Pesquisa Nacional sobre Acesso, Utilização e Promoção do Uso Racional de Medicamentos (PNAUM - Brazilian Survey on Access, Use and Promotion of Rational Use of Medicines), a population-based cross-sectional household survey, based on a probabilistic sample of the Brazilian population. We analyzed the association between low adherence to drug treatment measured by the Brief Medication Questionnaire and demographic, socioeconomic, health, care and prescription factors. We used Poisson regression model to estimate crude and adjusted prevalence ratios, their respective 95% confidence interval (95%CI) and p-value (Wald test). RESULTS The prevalence of low adherence to drug treatment for chronic diseases was 30.8% (95%CI 28.8-33.0). The highest prevalence of low adherence was associated with individuals: young adults; no education; resident in the Northeast and Midwest Regions of Brazil; paying part of the treatment; poor self-perceived health; three or more diseases; reported limitations caused by a chronic disease; using five drugs or more. CONCLUSIONS Low adherence to drug treatment for chronic diseases in Brazil is relevant, and regional and demographic differences and those related to patients' health care and therapy regime require coordinated action between health professionals, researchers, managers and policy makers.